2010
DOI: 10.1111/j.1365-2826.2009.01939.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photoperiod on Kisspeptin Neuronal Populations of the Ewe Diencephalon in Connection with Reproductive Function

Abstract: Kisspeptin (Kiss) is a key regulator of reproductive function in both prepubertal and adult mammals. Its expression appears to vary throughout the year in seasonal species. We aimed to determine the impact of a change of photoperiod on the size of Kiss neuronal populations found in the preoptic area (POA) and arcuate nucleus (ARC) of the ewe brain. Using immunocytochemistry, we first examined the proportion of neurones expressing Kiss, using HuC/D as a neuronal marker, at different time-points after transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 51 publications
5
36
0
Order By: Relevance
“…Furthermore, during the last week of lactation, Kiss1 mRNA in the arcuate nucleus was low in the AL-fed lactating rats and food-restricted dams, despite increases in overall LH concentrations. Increases in AVPV kisspeptin expression across pubertal development in rodents (Han et al 2005, Clarkson & Herbison 2006, Takase et al 2009, Clarkson et al 2010) and increases in POA kisspeptin expression across the photoperiodic transition from long days to short days in ewes (Chalivoix et al 2010) have been reported to be associated with the activation or reactivation respectively of the HPG axis. By contrast, in the AL-fed lactating rats, Kiss1 mRNA levels in the AVPV remained stable, between day 15 pp and day 20 pp, and were similar to those in the nonlactating controls, even though basal LH concentrations increased over this period.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, during the last week of lactation, Kiss1 mRNA in the arcuate nucleus was low in the AL-fed lactating rats and food-restricted dams, despite increases in overall LH concentrations. Increases in AVPV kisspeptin expression across pubertal development in rodents (Han et al 2005, Clarkson & Herbison 2006, Takase et al 2009, Clarkson et al 2010) and increases in POA kisspeptin expression across the photoperiodic transition from long days to short days in ewes (Chalivoix et al 2010) have been reported to be associated with the activation or reactivation respectively of the HPG axis. By contrast, in the AL-fed lactating rats, Kiss1 mRNA levels in the AVPV remained stable, between day 15 pp and day 20 pp, and were similar to those in the nonlactating controls, even though basal LH concentrations increased over this period.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown in sheep that there are more than 40 fewer ARC Kiss1-positive neurons during the non-breeding season compared with the breeding season [28] and that the expression of Kiss1 in the ARC is markedly decreased by transition of sheep from short days (8L:16D) to long days (16L:8D) [29], whereas that from long days to short days increases the number of kisspeptin-positive neurons by approximately 50% [30]. Therefore, although we did not examine histology in ewes in the breeding season, it is plausible to think that the population of kisspeptin neurons observed in this study would be still considerably smaller than that during the breeding season.…”
Section: Discussionmentioning
confidence: 99%
“…The intra-and inter-assay coefficients of variation of the control averaged 8% and 12%, respectively. Five ewes were killed on day 0 when LH levels were < 1 ng/ml for three consecutive samples (all our ewes had LH levels at 0 ng/ml on the day of killing) and five were killed on day 112 when LH levels were > 1 ng/ml for three consecutive blood samples (the mean LH concentration at D112 was 3.1 ng/ ml, with a maximum reaching 7.5 ng/ml in one ewe, as reported previously) (17).…”
Section: Animals and Treatmentsmentioning
confidence: 94%
“…Kiss is indeed one of the most potent stimulators of GnRH secretion, and is able to induce ovulation in ewes during both the breeding and anoestrous seasons (15). More interestingly, Kiss levels in the ARC fluctuate with photoperiod (16,17) and the number of Kiss appositions on GnRH neurones is seasonally regulated (16). Kiss neurones express a large number of oestrogen receptors a (18), although whether or not they may also be under the influence of thyroid hormones remains to be established.…”
mentioning
confidence: 98%